Prevenção da formação de hidratos em gasodutos submarinos - Eler, Jéssica Lopes Barbosa (2017)
Throughout the transport of natural gas in submarine pipelines to Processing Plants the industry may face several issues, including the hydrates formation. The submarine environment has favorable conditions of pressure (high) and temperature (low) to form these solid structures. Hydrates are critical issues to the flow assurance, as they can cause pipe obstruction, imprisonment, and drive problems in equipment, can compromise operations productivity, increase production costs and energy consumption, and cause damage to equipment and structures, compromising the safety of activities and, in more extreme cases, causing the complete production stoppage. Therefore, it is necessary to adopt measures for controlling, planning and monitoring the thermodynamic conditions in which the gas is being transported. In this paper is simulated the conditions close to the reality found during gas the transport of the natural gas produced at FPSO Cidade de Vitória Oil and Gas Production Plant to Cacimbas Gas Treatment Plant. The software HYSYS is used to verify the flow properties of the system, the temperature and the hydrate formation pressure, and to optimize the use of chemical methods (inhibitors) and thermal methods (heaters). The results obtained prove the efficiency of the thermodynamic inhibitor methanol in the prevention of hydrate formation and the flow rates needed to perform such control. In addition, the amount of energy required for an electric heater to provide sufficient heat to the pipe to prevent hydrate formation is indicated, showing that this thermal method can replace the methanol injection, but it is necessary to evaluate the energy requirement, which can be high.